2021
DOI: 10.3389/fphys.2021.624052
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Roles of the Renin Angiotensin System and Its Modulators During the COVID-19 Pandemic

Abstract: Since December 2019, the coronavirus 2019 (COVID-19) pandemic has rapidly spread and overwhelmed healthcare systems worldwide, urging physicians to understand how to manage this novel infection. Early in the pandemic, more severe forms of COVID-19 have been observed in patients with cardiovascular comorbidities, who are often treated with renin-angiotensin aldosterone system (RAAS)-blockers, such as angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs), but whether these are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 185 publications
(198 reference statements)
0
22
0
Order By: Relevance
“…Research on SARS-CoV-2 has brought forward evidence that the ACE2 receptor on lung alveolar epithelial cells is a central point for the cell entry of SARS-CoV-2 [ 21 ]. Therefore, many have been reluctant to use renin angiotensin system (RAS) agents for CVD patients who contract the virus, in fear that it would increase the viral load through upregulation of the ACE2 receptors found mainly in the airway epithelial cells [ 22 , 23 ]. ACE2 is an endogenous counter-regulator of RAS as its role is degrading Ang II to angiotensin 1–7; Ang II is a vasoconstrictor and is produced within RAS – the angiotensin converting enzyme (ACE) converts angiotensin I (Ang I) to Ang II [ 24 ].…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%
“…Research on SARS-CoV-2 has brought forward evidence that the ACE2 receptor on lung alveolar epithelial cells is a central point for the cell entry of SARS-CoV-2 [ 21 ]. Therefore, many have been reluctant to use renin angiotensin system (RAS) agents for CVD patients who contract the virus, in fear that it would increase the viral load through upregulation of the ACE2 receptors found mainly in the airway epithelial cells [ 22 , 23 ]. ACE2 is an endogenous counter-regulator of RAS as its role is degrading Ang II to angiotensin 1–7; Ang II is a vasoconstrictor and is produced within RAS – the angiotensin converting enzyme (ACE) converts angiotensin I (Ang I) to Ang II [ 24 ].…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%
“…In contrast, most observational studies which analyzed in-hospital exposure to RAS-blockers concluded in favor of a strong protective effect associated with treatment continuation [1,5]. However, among the myriad of observational studies published on RAS blockers and COVID-19 since the SARS-CoV-2 outbreak, many have suffered from important methodological limitations [6].…”
Section: Main Textmentioning
confidence: 99%
“…Two contradictory hypotheses emerged in the scientific literature. Some authors warned against the potential deleterious effect of RAS blockers, which had been shown to increase ACE2 expression in some animal models [1], and advocated for the preventive discontinuation of these drugs [2]. In contrast, others argued that RAS blockers may be beneficial against SARS-CoV-2-induced acute lung injury and should even be introduced in patients with COVID-19 [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations